Efficient xylem transport and phloem remobilization of Zn in the hyperaccumulator plant species Sedum alfredii. Issue 3 (20th February 2013) - Lu, Lingli; Tian, Shengke; Zhang, Jie; Yang, Xiaoe; Labavitch, John M.; Webb, Samuel M.; Latimer, Matthew; Brown, Patrick H.
Summary: Sedum alfredii is one of a few species known to hyperaccumulate zinc (Zn) and cadmium (Cd). Xylem transport and phloem remobilization of Zn in hyperaccumulating (HP) and nonhyperaccumulating (NHP) populations of S. alfredii were compared. Micro‐X‐ray fluorescence (μ‐XRF) images of Zn in the roots of the two S. alfredii populations suggested an efficient xylem loading of Zn in HP S. alfredii, confirmed by the seven‐fold higher Zn concentrations detected in the xylem sap collected from HP, when compared with NHP, populations. Zn was predominantly transported as aqueous Zn (> 55.9%), with the remaining proportion (36.7–42.3%) associated with the predominant organic acid, citric acid, in the xylem sap of HP S. alfredii . The stable isotope 68 Zn was used to trace Zn remobilization from mature leaves to new growing leaves for both populations. Remobilization of 68 Zn was seven‐fold higher in HP than in NHP S. alfredii . Subsequent analysis by μ‐XRF, combined with LA‐ICPMS (laser ablation‐inductively coupled plasma mass spectrometry), confirmed the enhanced ability of HP S. alfredii to remobilize Zn and to preferentially distribute the metal to mesophyll cells surrounding phloem in the new leaves. The results suggest that Zn hyperaccumulation by HP S. alfredii is largely associated with enhanced xylem transport and phloem remobilization of the metal. To our knowledge, this report is the first to reveal enhanced remobilization of metal by phloem transport in hyperaccumulators.